Construction model of excellent team for communication research institutes - Youli HUANG (Dianxin kexue)
Team is the forefront of scientific research institutes and the most active organizational unit, the effectiveness of team construction is directly related to the sustainable and healthy development of the entire enterprise. According to the characteristics of scientific research institutes, a model of team construction which was highly targeted,innovative and effective,was put forwand.Through the communication industry research institutes and telecom operators of the common and difference analysis, combined with the characteristics of the communications industry research institutes, excellent team construction model was put forward. Various effective measures of implementing outstanding team construction of scientific research institutes were further summed up. Finally, the effectiveness of the model was analyzed, and the results show that the model is effective in improving the train of thought,promoting the strategy execution ability and enhancing the creativity and cohesion of the research team.